Shifting Tides: The Impact of Zia Ul Haq's TV Commercial Ban on Pakistani Consumer Behavior (Journal of Asian Development Studies, 2025)
It looks at how the strict policies of Pakistani President Zia Ul Haq affected TV ads and how people behaved as consumers from 1977 to 1988. Zia took power in a military coup in 1977 and started a drive to make Pakistani culture and society more like Islam by imposing sharia law and harsher Islamic ideals. Zia was going to limit TV ads and other "vulgar, indecent, and provocative" media. The new rules had a big effect on advertising. It was no longer effective for ads to be racy, annoying, or directly promote products. Television ads had to follow Zia's "Islamic" culture, which limited their ability to be creative. Instead of Islamic symbols and teachings, ads with more complex and thought-provoking language were used. Communication about a brand turns into long PSAs about social issues instead of USPs. These changes to marketing messed up Pakistan's promotional habits. Zia's rules have changed how people think about and buy things. When ads were cleaned up, they made products and services unclear to customers. Through ads with a very religious tone, Zia's conservative social plan may have changed people's thoughts, tastes, and buying habits. Over time, these effects solidified new Islamic market cultures that were different from the more open-minded time before Zia's rule. This research paper looks at important policy frameworks, advertising strategies and styles, and consumer effects to give a more complete picture of how President Zia Ul Haq changed business expression, brand communication, and consumer behaviour in Pakistan. The study looks at the short- and long-term effects of Zia's controversial filtering.